The Global Economic Crisis and Trade and Growth Prospects in East Asia - Ylmaz Akyüz (Asian Development Bank (ADB), 2011)
The global economic crisis has revealed that growth in East Asia is highly vulnerable to slowdown in exports to major advanced economies. This paper shows that in precrisis years, at least one third of growth in the People's Republic of China was due to exports, and this proportion was even higher in most other East Asian economies. In the coming years the region may not be able to go back to rapid export-led growth because of sluggish growth and high unemployment in advanced economies, and the need to reduce trade imbalances in order to secure global stability and avoid frictions in the trading system. It will be necessary not only to rebalance domestic and external components of demand, but also to embark on industrial restructuring necessitated by a shift from export-led growth to growth led by domestic demand and intraregional trade.
hdl:11540/2052
Keywords: 330; Wirtschaftskrise; Internationale Konjunktur; Wirkungsanalyse; Handelseffekt; Wirtschaftswachstum; Ostasien